2023
DOI: 10.3389/fgene.2023.1173812
|View full text |Cite
|
Sign up to set email alerts
|

CircRNAs in osteoarthritis: research status and prospect

Abstract: Osteoarthritis (OA) is the most common joint disease globally, and its progression is irreversible. The mechanism of osteoarthritis is not fully understood. Research on the molecular biological mechanism of OA is deepening, among which epigenetics, especially noncoding RNA, is an emerging hotspot. CircRNA is a unique circular noncoding RNA not degraded by RNase R, so it is a possible clinical target and biomarker. Many studies have found that circRNAs play an essential role in the progression of OA, including … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 198 publications
(117 reference statements)
0
1
0
Order By: Relevance
“…It is known that circRNAs form a covalently closed loop and regulate gene expression, leading to governing cellular processes. Accumulating evidence has suggested that circRNAs play a critical role in osteoarthritis initiation and progression ( Wu and Zou, 2021 ; Wang et al, 2023 ; Li and Lu, 2023 ; Xue et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is known that circRNAs form a covalently closed loop and regulate gene expression, leading to governing cellular processes. Accumulating evidence has suggested that circRNAs play a critical role in osteoarthritis initiation and progression ( Wu and Zou, 2021 ; Wang et al, 2023 ; Li and Lu, 2023 ; Xue et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…В состав легочного сурфактанта человека входят 4 белка: SP-A, SP-B, SP-C, SP-D. Согласно нашим предыдущим исследованиям, на основе анализа структурной гомологии, было определено, что на лубрикативные свойств синовиальной жидкости могут оказывать влияние только SP-B, SP-C, SP-D [5]. Также особенности строения суставного хряща и наличие протеогликанов обеспечивают ему определенную защиту к избыточным механическим нагрузкам [6]. Среди протеогликанов особый интерес представляют такие белки, как лубрицин и аггрекан, поскольку именно их баланс, по современным представлениям, определяет прочностные и трибологические свойства суставного хряща [7].…”
unclassified